Review of Surfactant Use in Curcumin Drug Delivery System - Rostinawati, Titin; Sriwidodo, Sriwidodo; Susilawati, Yasmiwar; Ch., Anis Yohana (Jurnal Kartika Kimia, 2022)
Curcuminoids are the active components of the dried rhizome of Curcuma longa Linn. Curcuminoids consist of the three most basic constituents: curcumin, demethoxycurcumin, and bisdemethoxycurcumin. Traditionally, turmeric is widely used to treat flatulence, liver, menstrual disorders, hematuria, bleeding, and colic. With more research, turmeric's benefits are increasing, ranging from anti-inflammatory, cancer, autoimmune, neurological, cardiovascular disease, and diabetes. However, this is limited by the Physicochemical properties of curcumin which is not soluble in water; its metabolism is fast, and it is unstable in physiological pH and alkaline, causing low bioavailability and resulting in less optimal therapeutic effect. Currently, several drug delivery systems have been developed to improve the bioavailability of curcumin, such as adjuvants, liposomes, nanoparticles, curcumin-phospholipid complexes, curcumin structural analogs, micronization, and nanonization, Self Micro Emulsifying Drug Delivery Systems (SMEDDS), cyclodextrin inclusions, solid dispersions, nanoemulsions, nano balls, nanobeads, and nanofibers. Many of these preparations use the help of surfactants. Surfactants are used as emulsifiers, wetting agents, and solvents. In principle, surfactants help reduce surface tension and interfacial tension in gases, liquids, and solids, allowing these substances to diffuse and spread. Factors that must be considered when selecting a surfactant are the critical micelle concentration and the HLB value. Selection of the right surfactant will help increase bioavailability.